2007
DOI: 10.1111/j.1365-2656.2007.01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that niche specialization explains species–energy relationships in lake fish communities

Abstract: Summary1. Interspecific niche differences have long been identified as a major explanation for the occurrence of species-rich communities. However, much fieldwork studying variation in local species richness has focused upon physical habitat attributes or regional factors, such as the size of the regional species pool. 2. We applied indices of functional diversity and niche overlap to data on the species niche to examine the importance of interspecific niche differentiation for species richness in French lake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
158
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(176 citation statements)
references
References 74 publications
13
158
3
2
Order By: Relevance
“…2a), a pattern already documented for the regional flora of the French Alps (Boulangeat et al, 2012). At fine scales, greater niche partitioning is also expected when species richness (and possibly competition) increases (Mason et al, 2008). Here, we also found that specialist species tend to occur in richer assemblages (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…2a), a pattern already documented for the regional flora of the French Alps (Boulangeat et al, 2012). At fine scales, greater niche partitioning is also expected when species richness (and possibly competition) increases (Mason et al, 2008). Here, we also found that specialist species tend to occur in richer assemblages (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…A1), maybe reflecting that biogeographical differences and ecological processes (e.g. higher interspecific competition) at local or evolutionary scales lead to increased niche specialisation towards low latitudes, as has been found in several previous studies (Griffiths 2006, Reyjol et al 2007, Mason et al 2008, Tedesco et al 2012, Schleuter et al 2012, Cirtwill et al 2015.…”
Section: Discussionsupporting
confidence: 63%
“…Species-energy theories predict that low concentrations of oxygen, nutrients and solar energy could restrict primary production along the water column, which could lead to declines in species richness (Mason et al, 2008;Wright, 1983). Since many microbes in the ocean require oxygen for survival and growth, especially in important redox processes necessary for basic metabolism, DO in the water column is crucial to microbial communities in coastal ecosystems.…”
Section: G Lemaneiformis Cultivation Altered the Microbial Communitymentioning
confidence: 99%